Effects of 12 weeks of barefoot running on foot strike patterns, inversion eversion and foot rotation in long-distance runners - Latorre-Román, P. A.; Garcia-Pinillos, F.; Soto-Hermoso, V. M.; Muñoz-Jiménez, M. (Journal of Sport and Health Science, 2019)
Purpose: The purpose of this study was to determine the effects of 12 weeks of barefoot running on foot strike patterns, inversion-eversion and foot rotation in long-distance runners. Methods: Thirty-one endurance runners with no experience in barefoot running were randomized into a control group and an experimental group who received barefoot training. At pre-test and post-test, all subjects ran at low and high self-selected speeds on a treadmill. Data were collected by systematic observation of lateral and back recordings at 240 Hz. Results: McNemar's test indicated significant changes (p < 0.05) in the experimental group at both high and low speed running in foot strike patterns, reducing the percentage of high rearfoot strikers and increasing the number of midfoot strikers. A significant increase (p < 0.05) of external rotation of the foot and a decrease of inversion occurred at comfortable speed in the experimental group. Conclusion: Twelve weeks of barefoot running, applied progressively, causes significant changes in foot strike pattern with a tendency toward midfoot or forefoot strikes, regardless of running speed and significant changes in foot rotation at low speed, while the inversion was reduced in left foot at low speed with a tendency toward centered strike.